Cross‐border Healthcare in the EU: Welfare Burden or Market Opportunity? Evidence from the Spanish Experience. (10th November 2020) - Finotelli, Claudia
Abstract: EU citizens' access to social rights has become a contentious issue in the EU in the past decade. This article aims to reverse the North–South perspective on intra‐EU mobility and welfare by shifting the research emphasis from the labour‐oriented mobility of young Southern Europeans in Northern Europe to the non‐labour‐motivated mobility of Northern EU citizens in Southern Europe. To do so, this analysis addresses the provision of healthcare assistance regulated by European legislation for European retirees and patients in Spain. The analysis shows that retirement migration has been perceived as a state burden, yet patients' mobility has tended to be seen by the Spanish government as a market opportunity. However, the study also indicates that efforts to deal with these two different types of mobility are embedded in structural constraints that go beyond governments' intentions, which adds a new complexity to the limits of freedom of movement and EU citizenship.